Human leukocyte antigen (HLA) A-C-B-DRB1-DQB1 haplotype segregation analysis among 2152 families in China and the comparison to expectation-maximization algorithm result - Li, Yang; Chen, Lu-Yao; Zhang, Teng-Teng; Yuan, Xiao-Ni; Bao, Xiao-Jing; He, Jun (Chinese medical journal, 2021)
According to doctors’ typing applications and laboratory standard operation procedure, sequence-based typing plus sequence-specific oligonucleotide probe methods were performed for high-resolution HLA-A, B, C, DRB1, and DQB1 typing for all patients. [...]the patients’ typing results were used as phase-known and phase-unknown data to obtain observed and expected HFs, respectively, by the direct counting EM algorithm (only HFs >1 × 10–5 were outputted by Arlequin). The P values of the Chi-square test showed that there were no statistically significant differences between observed and expected haplotypes, not only in total overlapping data (P = 0.2424) and common data (HF ≥ 0.1%, P = 0.3698) but also in less-common data (HF < 0.1%, P = 0.1582). [...]the tendencies of observed and expected haplotypes are coincident, and the tendency concordance of common data is the best; then, the total overlapping data last the less common data. [...]EM could miss less-common real haplotypes but built incorrectly less-common haplotypes. [...]identifying less common haplotypes from segregation analysis must be used for checking and as supplements to cover the shortage of EM.